2016
DOI: 10.1016/j.mayocp.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic Microangiopathy Care Pathway: A Consensus Statement for the Mayo Clinic Complement Alternative Pathway-Thrombotic Microangiopathy (CAP-TMA) Disease-Oriented Group

Abstract: Thrombotic microangiopathies (TMAs) comprise a heterogeneous set of conditions linked by a common histopathologic finding of endothelial damage resulting in microvascular thromboses and potentially serious complications. The typical clinical presentation is microangiopathic hemolytic anemia accompanied by thrombocytopenia with varying degrees of organ ischemia. The differential diagnoses are generally broad, while the workup is frequently complex and can be confusing. This statement represents the joint recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 128 publications
(154 reference statements)
0
48
0
1
Order By: Relevance
“…Retrospective aHUS case series (prior to the availability of eculizumab) reported improved haematological parameters with PE, but long‐term outcomes were often poor . Thus, we do not support a recent US guideline recommending PE for ‘complement‐mediated TMA’, with substitution of eculizumab only in patients ‘refractory to or dependent on’ PE …”
Section: Evidence For Treatment Of Ahusmentioning
confidence: 58%
See 2 more Smart Citations
“…Retrospective aHUS case series (prior to the availability of eculizumab) reported improved haematological parameters with PE, but long‐term outcomes were often poor . Thus, we do not support a recent US guideline recommending PE for ‘complement‐mediated TMA’, with substitution of eculizumab only in patients ‘refractory to or dependent on’ PE …”
Section: Evidence For Treatment Of Ahusmentioning
confidence: 58%
“…The initial diagnosis of aHUS 9,25,[38][39][40] (or 'complementmediated TMA' 32 ) is currently based on exclusion of STEC-HUS and TTP, hence requiring confirmation of ADAMTS13 activity ≥10% (Fig. 1).…”
Section: Diagnosis Of Ahus Ahus As a Diagnosis Of Exclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial diagnosis of aHUS (or ‘complement‐mediated TMA’) is currently based on exclusion of STEC‐HUS and TTP, hence requiring confirmation of ADAMTS13 activity ≥10% (Fig. ).…”
Section: Diagnosis Of Ahusmentioning
confidence: 99%
“…The ADAMTS13 activity assay is increasingly being used to guide treatment decisions for patients with TMA . Many investigators have examined and confirmed the relationship between severe ADAMTS13 deficiency (activity levels of 10% or less) and a clinical diagnosis of TTP in patients with TMA .…”
mentioning
confidence: 99%